Effect of using various doses of Bromocriptine in estrus induction and subsequent fertility in lactating anestrus Iraqi Ewes: Al-Hamedawi, T. M.¹; Khammas, D. J.¹ and Mohammed, A. H.² - D. J., Khammas (The Iraqi Journal of Veterinary Medicine, 2017)
Forty eight (48) anestrus lactating Iraqi ewes aged between 2-4 years were undertaken 40 days postpartum in Babylon province (Technical institute in Al-Mussaib). Ewes were randomly divided into 4 equal groups according to type of treatment implemented. Group 1 (G1) were treated with vaginal sponges impregnated with 60 mg Medroxy Progesterone acetate for 10 days. Immediately after sponge removal, each ewe was injected IM. with 500 IU. Equine choriogonadotropines. Ewes of G2 were treated with Medroxy Progesterone acetate and Equine choriogonadotropines as mentioned above in addition n to 10 mg bromocriptine/day orally for 10 successive days at the same time of sponges insertion. Animals of G3 were treated with Medroxy Progesterone acetate and Equine choriogonadotropines in addition to 20 mg bromocriptine/day orally for 10 days. Ewes of G4 were treated with Medroxy Progesterone acetate and Equine choriogonadotropines in addition to 30 mg bromocriptine /day orally for 10 days. All ewes were mixed free with 5 fertile rams for 7 days after hormonal treatment to detect estrus and natural mating. Results showed that the duration of response to treatment was significantly longer P<0.05 in G1 (3.42±0.17) days than that recorded in G4 (1.14±0.12), G3 (1.20±0.21) and G2 (2.16±0.14) days. Consequently, the number of ewes which showed estrus was significantly high P<0.05 in G4 (100%) compared to G3 (75%), G1 (83.3%) and G2 (91.6%). The percentage of pregnancy was significantly higher P<0.05 in G3 (100%) versus 70%, 83.3% and 90.9% in G1, G4 and G2, respectively. Serum estrogen values were gradually increased with the increased doses of bromocriptine in all groups while progesterone value was decreased at the last days before sponges removal in all ewes.